Analysis of Implementation of Income Tax Incentives (PPh) Article 21 on the Level of Taxpayer Compliance at the Office of Tax Services, Counseling and Administration (KP2KP) of Magetan Regency - La Ode Abdullah; Ulfa Rahmawati; Halleina Rejeki Putri Hartono; Noviantika Dwi Elsarianti (International Journal of Business and Applied Economics, 2023)
This study aims to determine the mechanism for calculating Income Tax Article 21 before and after utilizing PPh 21 incentives and assessing its effectiveness at KP2KP Magetan. The data sources used are primary and secondary. The research population used is individual taxpayers who apply for income tax incentives. This sampling technique uses a non-probability method, namely purposive sampling. The analysis technique used is income tax calculation 21, calculation of the effectiveness ratio, and analysis of the results of the calculation of the effectiveness ratio. The results of this study indicate that the use of the PPh 21 incentive causes a difference between the Income Tax that must be deposited and the Tax Home Pay, namely that the amount of the Tax Home Pay of the taxpayer becomes larger than before using the 21 Income Tax incentive.